Blended finance to the rescue? Subsidies, vaccine bonds and matching funds in global health - Felix Stein; Desmond McNeill (Global Public Health)
To close persistent global health financing gaps, policymakers have in recent years promoted the idea of ‘blended finance’, i.e. the strategic use of public funds to attract additional private sector investment. To better understand this trend, this paper studies three major blended finance instruments, namely vaccine bonds, advanced market commitments, and matching funds. In doing so, this paper makes two important contributions. On a practical level, it shows that these three blended finance instruments tend to be expensive and of questionable effectiveness. Their high costs favour large corporate actors, private investors and middlemen, while their benefits for potential beneficiaries in low- and middle-income countries and for public donors remain unclear. On a theoretical level, the paper asks why these instruments remain popular in policy circles despite their shortcomings. It finds that blended finance mechanisms proliferate thanks to their seemingly innovative nature, a constant emphasis on urgency or crisis, and the promise of combining market-based self-interest with positive social impact. The paper ends on a call for much greater critical scrutiny concerning blended financing mechanisms.